Developing the future rural nursing workforce: report on a nursing roundtable. Issue 4 (August 2020) - Collett, Marjorie J.; Fraser, Claire; Thompson, Sandra C.
Abstract: Background: There are ongoing health workforce shortages in rural Australia with nurses a major component of the provision of health care. Training for nursing students in rural areas is one strategy to overcome this. Aim: To explore possibilities for nursing student rural clinical placements, with a view to increase the length of placements and strengthen the future rural nursing workforce. Methods: A Nursing Roundtable was held in regional Western Australia (WA) with representatives from five Western Australian universities, tertiary providers and service clinical stakeholders. Participants attended site visits to local facilities which included primary, community and hospital-based facilities. Findings: Major issues identified included short length of nursing placements; inflexibility of bookings via centralised placement databases; financial and family responsibilities inhibiting students taking up placements; quality of on-site supervision; and the availability of graduate programs after qualifying. Participants agreed longer student clinical placements reduced workload for academic and clinical staff allowing students to settle and be industry ready. Discussion: There was a strengthening of goodwill and willingness of university and clinical stakeholders to work collaboratively to lengthen student placements and consider placements in non-traditional settings to expand student understanding of career possibilities, rural and Indigenous communities, and the underpinning determinants of health. Conclusion: Back-to-back practicums or potential to share placements between different organisations were recognised as opportunities for further development. Efforts to increase placement length, broaden experiences and overcome financial barriers need to be addressed. Production of a marketing video to include job potential post-graduating was suggested to attract students.